Antimicrobial approaches against bacterial pathogens which cause lower respiratory system infections - Jozala, A. F.; Grotto, D.; Novaes, L. C.L.; de Carvalho Santos-Ebinuma, V. [UNESP]; Gerenutti, M.; Del Fiol, F. S. (Elsevier, 2016)
Usually, the health-care challenge in the respiratory infections is due to bacterial infections and their resistance to antimicrobials. These kinds of infections evolve rapidly, and for this reason inappropriate doses (for the broad-spectrum coverage) and extended time of therapy are applied. Inappropriate antimicrobial prescriptions have increased the pathogens resistance. On the other hand, the alternative therapies have grown rapidly over the last two decades to enhance the traditional medical practice in both America and Europe. In this chapter we have addressed different aspects of antimicrobial application against pathogens which cause lower respiratory infections. Moreover, we also discuss natural therapy by plants to treat these infections.
Keywords: antimicrobial; bacterial pathogens; natural medicine; plants